PERANCANGAN STRATEGI PENGEMBANGAN INDUSTRI KECIL DAN MENENGAH PADA SEKTOR INDUSTRI ALAS KAKI DI KECAMATAN CIKUPA TANGERANG KABUPATEN - Ahmad , Wakhit; Supriyadi, Edy; Eko, Kartiko (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
In the framework of the development of Small and Medium Industry (IKM) footwear industry that produces footwear and footwear daily needs as one of the potential impacts of local income support in Cikupa Tangerang District one of the eight provinces of Banten is part of this research. This study aims to find out about the design of IKM industry development strategy of footwear industry with competitiveness analysis and productivity. In an effort to develop SME industry sector footwear with SWOT analysis to get strategy. The relationship analysis used in this research uses Structural Equation Modeling using SmartPLS 2.0 software. The sample in this research is the perpetrators of IKM Shoes located in Kecamatan Cikupa Tangerang Regency amounting to 54 IKM produce footwear. Based on the results of smart PLS 2.0 is known that competitiveness significantly affects the development of SMEs in the footwear industry sector in the district of Tangerang. The relationship of competitiveness with productivity has a very significant relationship closely, whereas in the theory of diamond porter (1999) between factor conditions, demand conditions, related industry strategies, related industries and supporters, the role of government and opportunity factor is one that shows that no significant influence to the competitiveness of supporting industries with t-table values below <1.96. For factors that greatly affect competitiveness in industrial development is on the role of government. Thus expected under the role of government in Tangerang Regency in industrial development must be maintained and developed in support of industrial development programs, especially in IKM footwear industry sector.